Proceedings of the 4th International Conference on the Durability of Concrete Structures 2014
DOI: 10.5703/1288284315424
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of CFRP Plate in Simulated ICCP System of Concrete Structures

Abstract: An innovative effort was made to utilize carbon fiber reinforced polymer (CFRP) plate as an anode in impressed current cathodic protection (ICCP) of reinforced concrete structure. The feasibility was explored by bonding CFRP strips to concrete and then applying protection current through CFRP strips to steel rebar in concrete. Service life and performance of CFRP plate were investigated in simulated ICCP systems with various configurations. Steel potential results confirmed that the steel rebar in concrete mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Through a combined SEM-EDS analysis, the treated CFRP was inferred to be structurally intact. However, it should be noted that the carbon fibers could severely degrade if they were immersed in the chloride-contaminated and Ca(OH) 2 solution with a much larger current density [20].…”
Section: Post-treatment Microscopic Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Through a combined SEM-EDS analysis, the treated CFRP was inferred to be structurally intact. However, it should be noted that the carbon fibers could severely degrade if they were immersed in the chloride-contaminated and Ca(OH) 2 solution with a much larger current density [20].…”
Section: Post-treatment Microscopic Examinationmentioning
confidence: 99%
“…Gadve et al [18,19] presented ICCP tests using a CFRP as the anode. Recently, Zhu et al [20] investigated the behavior of a CFRP anode in a simulated ICCP system. No significant degradation in electrical and mechanical properties was observed for a CFRP subjected to anodic polarization at the selected applied current density.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial CFRP strips were used in this study, since this kind of material maintained good performance as anode in previous studies [ 21 ]. According to the information given by the manufacturer, CFRP strips are made of multi-layer carbon fibers bounded by LAM-125/LAM-226 laminating epoxy (Pro-Set Inc., Bay City, MI, USA).…”
Section: Experimental Programmentioning
confidence: 99%
“…Recently, Zhu et al . [ 21 ] investigated the behavior of CFRP anode in the simulated ICCP system. No significant degradation in electrical and mechanical properties was found of CFRP subjected to anodic polarization at the selected applied current densities, which demonstrated that CFRP could be successfully used to simultaneously carry out the dual functions of impressed current anode and structural strengthening.…”
Section: Introductionmentioning
confidence: 99%
“…However, besides the electric conductivity, the successful application of ICCP also depends significantly upon the correct operation of the anodes, the cost of the anode material and their service life or rate of consumption due to a number of environmental and operational factors. The feasibility of using CFRP as the anode material in ICCP has been proven by Nguyen et al (2012), Zhu et al (2014aZhu et al ( , 2014b, Lambert et al (2015) and Verma and Goyal (2015). Though CFRP has ageing problem, the previous studies (Zhu et al 2017) found that CFRP would not be damaged if the current density applied in the ICCP system is carefully chosen and the service life of CFRP anode could be up to 40 years.…”
Section: Introductionmentioning
confidence: 99%